Insurers' intervention, separation of two rights and firm's technology innovation - Xu, Bin; Hao, Fangjing (Frontiers in Public Health, 2023)
This paper takes insurers' intervention as the entry point, and sets insurers' intervention, separation of two rights and firms' technological innovation in a specific context to study the transmission mechanism and economic consequences using panal model. The results show that there is a positive relationship between insurers' intervention and firm's technological innovation, and the degree of separation of two rights has a negative moderating effect on the relationship between insurers' intervention and technological innovation, and this effect is more obvious in the sample of state-owned enterprises. Therefore, the state should formulate relevant policies to guide the equity investment behavior of insurance companies so as to improve the operational efficiency of market resources.